PENINGKATAN CBR DAN PENURUNAN POTENSI PENGEMBANGAN PADA TANAH DENGAN STABILISASI DIFA SOIL STABILIZER - Nizar Firdaus; Athaya Zhafirah (Racic : Rab Construction Research, 2023)
It is vital to know the bearing capacity of the soil prior to construction which can be determined from the CBR. CBR is an essential parameter in evaluating the soil bearing capacity. CBR increase can be done through stabilization. Stabilization is carried out chemically by adding an additive, a difa soil stabilizer, into the soil with a specific composition. This study aimed to determine the increase in CBR and decrease in swelling potential in soils added with DSS. The tests carried out were compaction and CBR-soaked conditions with immersion for four days. The composition of the difa soil stabilizer used in this study was 0%; 2.5%; 5%; and 7%. In addition to difa soil stabilizer, 8% cement is also added to the soil. The results obtained from this study were that adding 8% cement and 2.5% and 5% difa soil stabilizer increased the CBR value to 57%. In comparison, adding 8% and 7% difa soil stabilizer reduced the CBR value to 38%.